Stabilization of the offset frequency of an all polarization-maintaining fiber erbium frequency comb - Sinclair, L. C.; Coddington, I.; Swann, W. S.; Newbury, N. R. (CLEO: 2013, 2013)
We demonstrate a completely polarization-maintaining fiber frequency comb operating at a 200 MHz repetition rate and show initial phase-locking of the carrier-envelope offset frequency. This design is compatible with a robust, fieldable frequency comb. Work of the U.S. government, not subject to copyright.